2011
DOI: 10.1038/srep00087
|View full text |Cite
|
Sign up to set email alerts
|

The time variation of dose rate artificially increased by the Fukushima nuclear crisis

Abstract: A car-borne survey for dose rate in air was carried out in March and April 2011 along an expressway passing northwest of the Fukushima Dai-ichi Nuclear Power Station which released radionuclides starting after the Great East Japan Earthquake on March 11, 2011, and in an area closer to the Fukushima NPS which is known to have been strongly affected. Dose rates along the expressway, i.e. relatively far from the power station were higher after than before March 11, in some places by several orders of magnitude, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
60
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(62 citation statements)
references
References 13 publications
(16 reference statements)
2
60
0
Order By: Relevance
“…We calculated the direct effects of radiolysis on antioxidant concentrations at a total (external þ internal) radiation dose rate of 417 mGy h 21 low LET radiation, representative of the highest doses to organisms in the Chernobyl zone (see electronic supplementary material) and also relevant to current contamination densities and dose rates at Fukushima [14]. No significant changes in antioxidant concentrations or cellular redox potential were calculated.…”
Section: Discussionmentioning
confidence: 99%
“…We calculated the direct effects of radiolysis on antioxidant concentrations at a total (external þ internal) radiation dose rate of 417 mGy h 21 low LET radiation, representative of the highest doses to organisms in the Chernobyl zone (see electronic supplementary material) and also relevant to current contamination densities and dose rates at Fukushima [14]. No significant changes in antioxidant concentrations or cellular redox potential were calculated.…”
Section: Discussionmentioning
confidence: 99%
“…In the early stages of radiation exposure following the FDNPP accident, short-lived radionuclides such as 132 Te and 133 Xe were observed (9,10) and were noted as a major source of external exposure. The outdoor external dose rate within 80 km of the FDNPP decreased by 11% from June to November 2011 (i.e., less than 1 y after the accident) owing to the physical decay of 134 Cs (half-life of 2.07 y) and weathering (11); however, radiation exposure from deposited 137 Cs (half-life of 30.2 y) (i.e., groundshine) will persist long term.…”
Section: Significancementioning
confidence: 99%
“…The values obtained in the car-borne survey indicate the radiation dose along paved roads, which are covered by asphalt. According to previous reports, 3,20) the observation of lower dose rates over sealed surfaces can be explained by easier removal of deposited radionuclides from them. Contamination in the air can be eliminated away more easily by rain and is also diluted by resuspension from wind, which is easier along sealed surface by concrete/asphalt rather than unsealed surface such as forested areas where contamination adheres to soil particles and plants.…”
Section: Estimation Of Absorbed Dose Rate In Airmentioning
confidence: 99%
“…Thus, car-borne surveys of radiation doses in the environment have been conducted by many research groups. 3, 6, 11~13) HOSODA et al 3) reported that the highest dose rate of 36 Gy h -1 was measured in Namie Town on April 11 th , 2011. Furthermore, a similarly high value of more than 30 Gy h -1 was measured in Akougi, Namie Town on April 18 th -21 st , 2011.…”
Section: )mentioning
confidence: 99%
See 1 more Smart Citation